A comparative study of experimental optimization and response surface optimization of Cr removal by emulsion ionic liquid membrane - Goyal, R.K.; Jayakumar, N.S.; Hashim, M.A. (Elsevier, 2011)
A comparative study on the optimization of process parameters of an emulsion ionic liquid membrane (EILM) by experimental work and response surface methodology (RSM) has been carried out. EILM was prepared by using kerosene as solvent, Span 80 as surfactant, NaOH as internal reagent, a hydrophobic ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([BMIM](+)[NTf(2)](-)) as a stabilizer and a second ionic liquid tri-n-octylmethylammonium chloride (TOMAC) as a carrier. The prepared EILM was used to separate and concentrate Cr from wastewaters. The comparison between the experimentally optimized and the RSM optimized values was accomplished by optimizing the following parameters: homogenization speed, carrier concentration, internal phase concentration, agitation speed, treat ratio, internal to membrane phase ratio, surfactant concentration and pH of the feed phase. The comparison showed that all the values were in good agreement except for the internal phase concentration and the treat ratio. It was observed that the stability provided by [BMIM](+)[NTf(2)](-) decreased as the extraction progressed due to its high density. Nevertheless, a good stability could be obtained by the combination of [BMIM](+)[NTf(2)](-) and Span 80 during extraction process.